A Prospective Cross-Sectional Study of the Spectrum of Gallbladder Masses on Computed Tomography, Confirmed by Histopathological Examination at a Tertiary Care Centre in Eastern India. - Suruthi T I; Kumar, Amit; Prasad, Umakant; Kumar, Bipin (Student’s Journal of Health Research Africa, 2025)
Introduction: Gallbladder carcinoma is the most common malignancy of the biliary tract and is often diagnosed at an advanced stage due to non-specific clinical symptoms. Early and accurate imaging is crucial for timely diagnosis and appropriate surgical planning. This study aimed to evaluate the structural and enhancement characteristics of gallbladder masses using Multi-Detector Computed Tomography (MDCT) and to correlate the imaging findings with histopathological results. Methodology: A prospective cross-sectional diagnostic study was conducted in the Department of Radio-diagnosis at Indira Gandhi Institute of Medical Sciences (IGIMS), Patna. A total of 200 patients with clinically or sonographically suspected gallbladder cancer were enrolled between July 2021 and June 2022. All patients underwent contrast-enhanced MDCT using a Toshiba Aquilion 128-slice scanner. Imaging findings—including tumor morphology, local invasion, lymph node involvement, vascular encasement, and resectability—were recorded. Results: The mean age of the study population was 54.16 years, with a female predominance (70%). Common CT findings included focal irregular wall thickening (33.5%), sessile intraluminal polyps (27.5%), and masses replacing the gallbladder fossa (24.5%). Liver invasion was observed in 81% of cases, and lymph node metastases in 44.5%. Only 28% of patients had resectable disease at diagnosis. Histopathology revealed that moderately differentiated adenocarcinoma was the most frequent type (51.5%). MDCT demonstrated a sensitivity of 100%, specificity of 73.08%, and diagnostic accuracy of 96.5%. Conclusion: MDCT is a highly sensitive imaging modality for evaluating suspected gallbladder malignancies. It plays a critical role in tumor staging, assessing local extension, and determining operability. However, due to late-stage presentation, the majority of cases remain unresectable at the time of diagnosis. Recommendation: In endemic regions for gallbladder cancer, early screening through ultrasound followed by contrast-enhanced CT imaging is recommended to facilitate earlier detection and improve surgical outcomes.